THE EFFECTIVENESS OF USING THE SCIENCE KIT THROUGH DEMONSTRATION METHODS AGAINST THE BASIC PROCESS SKILLS OF GRADE V STUDENTS OF SD AISYIYAH 1 MATARAM - Haifaturrahmah Haifaturrahmah (Jurnal Dikdas, 2019)
The Purpose This study aims to determine the effectiveness of the use of Natural Science KIT to improve the basic science skills of fifth grade students in SD Aisyiyah 1 Mataram through demonstration learning methods. This type of research is a One Group Pretest-Posttest Design experiment. The subjects in this study were fifth grade students at SD Aisyiyah 1 Mataram in the 2018/2019 academic year, totaling 28 students. The basic science process skills observed are observing, communicating, classifying, measuring, differentiating, and predicting. From the results of the study, the skills to enter are still in the low category, while the other five skills are in the medium category